UPAYA KEPALA MADRASAH DALAM MENINGKATKAN PENGUATAN KARAKTER SISWA DI SEKOLAH - Aufa, Najia Barouatul; Siregar, Afnita Marni; Mariana, Wina; Ikhsan, Basthotum (IKAMAS: Manajemen Pendidikan Islam, 2022)
Character education has a higher meaning than moral education, because character education is not only related to the problem of right and wrong, but how to instill habits (habits) about good things in life so that children or students have awareness, and understanding that lives and concern and commitment to apply banking in daily life. The research method used is qualitative in the form of descriptive analysis. This study seeks to describe or describe what is being studied regarding the principal's strategy in strengthening the character education of students at MTs. Muallimin UNIVA Medan.